Idah Bagi Suami Dalam Konsep Hermeneutika Maqāṣidī Dan Relevansinya Dengan Pembaruan Hukum Keluarga (Studi Atas Surat Edaran Dirjen Bimas Islam Nomor P-005/Dj.Iii/Hk.007/10/2021) - Ahmad Ahda Sabila (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This article aims to examine the concept of idah for husbands in the perspective of hermeneutics maqāṣidī and its relevance to the reform of Islamic family law. This is motivated by the problem of idah which has been only required for women, while men are not, so a new interpretation is needed to achieve gender equality in the application of idah. One of the reform efforts is the issuance of the Circular Letter of the Director General of Bimas Islam Number P-005 / DJ. III/Hk.007/10/2021 related to marriage when the wife is undergoing the idah period. This research is a literature study using the hermeneutics maqāṣidī approach to analyze the concept of idah and its relevance to efforts to reform family law. The results showed that the concept of idah for husbands in the perspective of hermeneutics maqās}idī has relevance to the purpose of family law reform, especially related to improving the status of women, and shows that the waiting period (idah) is not only imposed on women, but can also be imposed on men (ex-husbands). This is a form of equality and justice in the application of idah, in accordance with the purpose and wisdom of the declaration of idah. The Circular Letter related to marriage when the wife undergoes the idah period indirectly indicates a waiting period for the ex-husband, which provides an element of equality and justice. It is seen as a form of extracting implicit meaning (secondary meaning) from the concept of idah involving understanding socio-historical settings. The implementation of idah for husbands can be one of the efforts to reform Islamic family law in Indonesia that realizes justice and gender equality. This can reduce the injustice that has occurred so far, where only women are charged with idah obligations, while men are not.